A simple and sustainable beamhouse by the recycling of waste-water from KCl-dispase synergistic unhairing in leather making. (1st February 2021) - Liu, Hui; Li, Xiumin; Li, Mengya; Zhang, Yafei; Tang, Keyong; Liu, Jie; Zheng, Xuejing; Pei, Ying
Abstract: The conventional beamhouse of leather making invariably results in serious pollution of sulfide, solid suspension and ammonia nitrogen because of the use of Na2 S and Ca(OH)2 in unhairing (liming) and reliming. It is an urgent issue to develop alternatives of the Na2 S and Ca(OH)2 system. In this work, the K + and Cl − of Hofmeister series are chosen to improve the binding ability of dispase to water molecules and substrate, which can further enhance the unhairing/fiber opening effect of dispase, with only one step for unhairing, opening collagen fiber-bundles and bating. The cycle unhairing effect of K + /Cl − /dispase solution system and its unhairing waste-water recycling in fiber opening are studied. The effect of K + and Cl − on the penetration of dispase in bovine hides, the hydrolysis for proteoglycans and elastic fibers, and the opening effect for collagen fiber-bundles are analyzed systematically. The results indicated that, the K + and Cl − increase the stability of dispase activity to 12 times of recycling for unhairing. Due to the electrostatic attraction of K + and Cl − to the charged amino acid residues, both the penetration of dispase in bovine hides and the hydrolysis of proteoglycans and elastic fibers are accelerated, and an easy step for unhairing/fiber opening is realized. Only 30 h is needed for unhairing/fiber opening, and the waste-water can be recycled for unhairing too. Because of the reuse of unhairing waste-water, low pollutant loads, high collagen fibril dispersity are reached. The resultant leathers are good in physical properties, and their thermal stability are comparable to that by the conventional process. The leather making system of KCl/dispase is suggested to be a cleaner and greener technology than the conventional ones. Highlights: KCl is used to keep the activity and help the penetration of dispase in bovine hides. Dispase is FITC-labeled to study the mechanism of KCl-dispase synergistic unhairing and fiber opening. Unhairing waste-water is reused for cyclic unhairing and fiber opening. One step beamhouse is realized by KCl-dispase system instead of unhairing (liming), reliming deliming and bating.